Encouragement is not Enough: Addressing Social and Structural Barriers to Female Recruitment. Issue 4 (16th December 2015) - Dittmar, Kelly
Abstract : Invite a woman to run for office. Based on findings that women are most responsive to and reliant on encouragement in making the decision to run for office, this invitation refrain is pervasive among those seeking greater gender parity in U.S. politics. For example, in 2007, the Women's Campaign Fund launched She Should Run, complete with an online tool that, to date, has been used to ask just under 200, 000 women to run for office. In 2014, another organization, Vote Run Lead, adopted a similar strategy, launching Invitation Nation to send e-invitations to run to nearly 10, 000 women within their first year of launching the project. My own organization, the Center for American Women and Politics (CAWP), has "invited" countless women to run for office through online communications, training programs, and recruitment campaigns and initiatives. While each of these organizations has also sought to provide potential women candidates with training, information, and resources to assist them throughout the recruitment process, our obsession with inviting can constrain a more complex and comprehensive approach to female candidate recruitment in both research and practice.